DCF DAN RELATIVE VALUATION UNTUK MENGESTIMASI SAHAM PT. ATLAS RESOURCES DALAM IPO - Rifki Khoirudin (Universitas Ahmad Dahlan, 2014)
This research aims to estimate fair value per share of PT. Atlas Resources, Tbk. as a comparison value to the offered price, set at the time of Initial Public Offering (IPO). This research also aim to determine whether the price offered abovementioned were undervalued or overvalued. Information used in this research is in the form of secondary data of PT. Atlas Resources, Tbk.fi nancial statements for the period of fourth years from 2007 to 2011 which was audited by public accountants collectively with other information contained in yhe its prospectus, fi nancial report of comparable companies, and stock prices of comparable companies. The analyzing tools used to determine the fair value per share are discounted cash fl ow method and relative valuation method. The discounted cash fl ow method were perform via: projection of the financialÂ statements i.e. the balance sheet and income statement, projection of Free Cash Flow to Equity (FCFE), determination of the discount rate, determination of terminal value, and determining the estimated value of the equity. The relative valuation method is established by searching, choosing and determining the appropriate multiple of comparable companies in similar bussines. Multiples used are: Price Earnings Ratio (PER), Price to Book Value (PBV), and Price to Sales Ratio (P/S).